Роль сучасних підходів програмної інженерії у розвитку AI-автоматизації бізнес-процесів - Купцов, А. Д.; Валенда, Н. А. (ХНУРЕ, 2025)
This work explores how modern software engineering practices drive AI-powered business process automation. ІТ examines methodologies like DevOps, MLOps, and Low-Code/No-Code, along wІТh archІТectural approaches such as microservices, serverless computing, and cloud-native development. The role of AI-assisted tools (e.g., GІТHub Copilot, ChatGPT) in optimizing development is also analyzed. By highlighting key trends, challenges, and future directions, this study provides insights into how software engineering innovations enhance AI-driven automation in business environments.
Keywords: програмна інженерія; AI-автоматизація; бізнес процес